‘Gemoy’ Campaign: A Strategic Electoral Communication of Prabowo Subianto - Annisa, Lintang; Maghfira, Sabrina Rahmadhanty (Future Science / FSH-PH Publications, 2025)
Prabowo Subianto, an ambitious politician in Indonesia, ran for the presidency in the 2024 election after experiencing defeats in 2014 and 2019. This study examines the strategic political communication of Prabowo Subianto during the 2024 Indonesian presidential elec-tion, focusing on his rebranding efforts and digital media strategies. The objective of this research is to analyze how Prabowo’s strategic communication shaped public perception and attracted a broader voter base. This study employs a case study approach by analyzing campaign materials, social media content, and public discourse to assess Prabowo’s strategic communication transformation. Data sources include digital media analysis, interviews with political ana-lysts, and public opinion surveys. The findings indicate that Prabowo successfully transformed his image from a rigid military figure to a more approachable and humorous persona through digital communi-cation strategies. The